2023
DOI: 10.1002/aenm.202204247
|View full text |Cite
|
Sign up to set email alerts
|

Surface Regulation with Polymerized Small Molecular Acceptor Towards Efficient Inverted Perovskite Solar Cells

Abstract: Optimizing the interface between the perovskite and transport layers is an efficient approach to promote the photovoltaic performance of inverted perovskite solar cells (IPSCs). Given decades of advances in bulk materials optimization, the performance of IPSCs has been pushed to its limits by interface engineering with a power conversion efficiency (PCE) over 25% and excellent stability. Herein, an n‐type polymeric semiconducting material, PY‐IT, that has shown remarkable performance in organic photovoltaics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 96 publications
0
23
0
Order By: Relevance
“…In recent years, organic–inorganic hybrid perovskite solar cells (PSCs) are becoming a research hotspot in the field of photovoltaic energy, because their certified photoelectric conversion efficiency (PCE) has reached 26.1%, which is equivalent to that of commercial silicon-based solar cells. The realization of this excellent PCE can be attributed to the numerous advantages of perovskite crystals, including broad spectral response, tunable optical band gap, high defect tolerance, small exciton binding energy, long carrier diffusion distance, and so forth. However, the weak binding and ion–electron characteristics of perovskite crystals inevitably cause high-density defects, which leads to significant nonradiation recombination and reduces the overall reliability of the device. , …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, organic–inorganic hybrid perovskite solar cells (PSCs) are becoming a research hotspot in the field of photovoltaic energy, because their certified photoelectric conversion efficiency (PCE) has reached 26.1%, which is equivalent to that of commercial silicon-based solar cells. The realization of this excellent PCE can be attributed to the numerous advantages of perovskite crystals, including broad spectral response, tunable optical band gap, high defect tolerance, small exciton binding energy, long carrier diffusion distance, and so forth. However, the weak binding and ion–electron characteristics of perovskite crystals inevitably cause high-density defects, which leads to significant nonradiation recombination and reduces the overall reliability of the device. , …”
Section: Introductionmentioning
confidence: 99%
“…[23] Chen et al introduced an organic semiconducting nonfullerene molecule YTh2 to minimize the defect states and enhance the operational stability, resulting in a PCE of 21.5% and maintaining 82.8% of its initial PCE upon exposure to ambient air over 1600 h. [24] Evidently, the nonfullerene semiconducting molecules can combine defects passivation and electron extraction, creating favorable conditions for improving the photovoltaic performance of perovskite devices. [25] Herein, we first introduced a conjugated nonfullerene molecule (IO-4Cl) with n-type semiconductor property into TPSCs to enhance the efficiency and moisture stability simultaneously. Theoretical calculations and experimental characterizations revealed that IO-4Cl possessing electron-rich units (C=O group) could passivate the defects of tin-based perovskite film through the formation of Lewis adduct, thereby suppressing the nonradiative recombination efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, Li et al and Hong et al introduce N-type small molecules to optimize the perovskite/ETL interface, increase the charge transfer channel, and adjust the energy-level distribution. 16,17 Unfortunately, the small molecules at the perovskite/ETL interface can be easily destroyed and spread upward or downward, which negatively affects the photovoltaic performance and working stability of p–i–n PSCs. Therefore, it is urgent to develop an in situ passivation technology to regulate the energy levels near the top surface in p–i–n PSCs.…”
Section: Introductionmentioning
confidence: 99%